PSYCHOLOGICAL EFFECT OF CAPTIVITY TO THE PROTAGONIST IN EMMA DONOGHUE’S NOVEL ROOM - Trivani Desyara; Zulfan Sahri (Universitas Islam Sumatera Utara, 2020)
This research aims at identifying, analyzing and describing the psychological condition in Room by Emma Donoghue, and also the causes and effects of the problem which are described in this novel. In the novel, the writer analyze the problem by using theory of Islam (2007), Jung in Emir (2016), and Van Dijk (1997) which explains about psychological effect, psychology, and captivity. This thesis uses qualitative method in analyzing the data to be flatly described to show the evidence of the data identified from the novel. The analysis is conducted by classifying the obtained data in chapter four related to the problems of the study. Hence, there are two kinds of psychological effect and three causes of the effect to be analyzed, i.e. social anxiety disorder and posttraumatic disorder, and the causes are: held captive, domination of Old Nick and hard attempt to escape. The results of this study depict that someone who has a mental illness within himself is not spared from the causes behind them, and be brave to get out from comfort zone to be a better version of your life like what is done by Jack by bravely escaping from the room.